Developing credit based micro-credentials for the teaching profession: An Australian descriptive case study. Issue 7 (3rd October 2021) - White, Simone
ABSTRACT: The impact of the pandemic has revealed just how important teachers are to a nation's economic productivity and to the very social fabric and well-being of any society. It has also revealed more starkly the socio-economic and digital divides that teachers continue to address daily to support student learning. How then, to best support teachers own professional learning in complex times? This is a question that has long been asked—but now requires a new framing against the backdrop of constant technological change and disruption. This paper reports on a descriptive case study exploring and critiquing the approach to building a set of credit-bearing micro-credentials for teachers continuing professional development in the Australian context. The set of micro credentials were designed to both support teacher's professional learning in a set of key learning fields and to enable them to build pathways to further Graduate and Master of Education Studies. The study documents the various stages of design and development drawing from the literature and provides some early findings of the affordances and challenges of establishing further micro credentials for the teaching profession.